Bacterial susceptibility in bloodstream infections: Results from China Antimicrobial Resistance Surveillance Trial (CARST) Program, 2015–2016. (June 2019) - Zhang, Fan; Li, Yun; Lv, Yuan; Zheng, Bo; Xue, Feng
Highlights: A total of 1758 strains of various types with the sum ≥ 30 were isolated from blood specimens. All the clinical isolates were collected from 18 hospitals in mainland China. Extended-spectrum β‑lactamase-negative Klebsiella pneumoniae were subdivided into carbapenem sensitive and nonsensitive. The resistance rates of Klebsiella pneumoniae to carbapenems were 16.2–17.4%, which have risen very quickly in recent years. Abstract: Objectives: The aim of this study was to monitor the trends in antimicrobial resistance from the blood samples isolated from the Chinese mainland. Methods: All clinical isolates were collected from 18 hospitals. The minimal inhibitory concentrations (MICs) were tested in a central laboratory using the agar dilution method recommended by the Clinical and Laboratory Standards Institute. The susceptibilities of isolates to antimicrobial agents were determined by using Clinical and Laboratory Standards Institute or European Committee on Antimicrobial Susceptibility Testing (EUCAST) 2017 guidelines. Results: A total of 1758 strains of various types with the sum ≥ 30 were isolated from blood specimens in 2015–2016. The detection rates of extended-spectrum β-lactamases (ESBLs) among Escherichia coli were 55.6%, whereas those in Klebsiella pneumoniae were 22.4%. Carbapenems, moxalactam, tigecycline, and amikacin displayed desirable antibacterial activity against Enterobacteriaceae, but a significant increase in Klebsiella pneumoniae to carbapenems was noted. Nonfermenters were highly resistant to carbapenems, especially in Acinetobacter Baumannii isolates, >70％ of which were resistant. The prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) reached 36.1% and 90.4%, respectively. Staphylococcus aureus had 100% susceptibility to vancomycin. Enterococcus faecium isolates showed significantly higher resistant rates to most of the tested antimicrobial agents than Enterococcus faecalis isolates. While vancomycin-resistant Enterococcus (VRE) was 3.28%, the non-susceptible rate of linezolid to Enterococcus faecalis was 6.8%. Conclusions: This study revealed the major bacterial pathogens' antibiotic susceptibility patterns involved with bloodstream infection in mainland China.